Socioeconomic Conditions of Migrants and Non-Migrants in Haryana - Khurana, Manvi; Bedi, Jatinder S. (Arthshastra Indian Journal of Economics & Research, 2023)
Purpose : Internal migration is considered an essential factor that significantly affects the origin and destination areas in varying degrees depending upon the employment situation in the destination region and the characteristics of migrants themselves. Haryana has the highest per-capita income among the major states in India and witnessed increased mobility over the years due to its advanced agricultural base, highly developed industrial sector, and proximity to the National Capital Region. Therefore, the present study examined the socioeconomic conditions of migrants and non-migrants in Haryana. Methodology : The study is based on secondary as well as primary data. The survey was conducted in four districts randomly selected in the state. A total of 509 households were surveyed from June 2021–February 2022. A detailed questionnaire was used to collect information about the socioeconomic conditions of the migrants and non-migrants. The collected data were analyzed using appropriate statistical techniques. Findings : The results suggested that most migrants were male heads of households who moved for work/employment to provide better living conditions. There were wide variations among inter-state and intra-state migrants. The level of education was significantly lower among inter-state migrants compared to non-migrants and intra-state migrants. Most inter-state migrants’ heads of households were illiterate or literate up to the middle, employed as daily wage casual laborers working in the informal sector, and living in precarious conditions. Such workers generally suffered from low earnings, lack of stability, and durability of employment. The average monthly household income and expenditure of the inter-state migrant household were lower than that of the non-migrants. The reason for low per capita household consumption among inter-state migrant families was that some portion of their relatively low income was also repatriated to the point of origin. Practical Implications : The findings highlighted that inter-state migration plays an important role in developing the state’s economy by providing cheap and flexible labor ready to take up any work. Originality : This is the only study that attempted to examine the socioeconomic conditions of migrants in various districts of Haryana and their comparison with non-migrants.